2001
DOI: 10.1021/bi0103819
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes of pharaonis Phoborhodopsin upon Photoisomerization of the Retinal Chromophore:  Infrared Spectral Comparison with Bacteriorhodopsin

Abstract: Archaeal rhodopsins possess a retinal molecule as their chromophores, and their light energy and light signal conversions are triggered by all-trans to 13-cis isomerization of the retinal chromophore. Relaxation through structural changes of the protein then leads to functional processes, proton pump in bacteriorhodopsin and transducer activation in sensory rhodopsins. In the present paper, low-temperature Fourier transform infrared spectroscopy is applied to phoborhodopsin from Natronobacterium pharaonis (ppR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
230
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(259 citation statements)
references
References 58 publications
27
230
0
2
Order By: Relevance
“…FTIR spectroscopy was performed as described previously (19,20). Ninety microliters of the SRII sample was dried on a BaF 2 window with a diameter of 18 mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FTIR spectroscopy was performed as described previously (19,20). Ninety microliters of the SRII sample was dried on a BaF 2 window with a diameter of 18 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Ninety microliters of the SRII sample was dried on a BaF 2 window with a diameter of 18 mm. The dry film was then rehydrated by putting an ∼1 µL drop of water beside the film and sealing with another window and a silicon rubber O-ring (19,20). After hydration, the sample was placed in a cell, which was mounted in an Oxford DN-1704 cryostat placed in the Bio-Rad FTS-40 spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…Binding Analysis and FTIR Measurements-SRII and HtrII-(1-159) proteins were prepared as described previously (26,27). A truncated HtrII protein expressed from position 1 to position 159, which has been shown to exhibit the same interaction with SRII as the full-length protein (28,29), was used for measurements other than phototaxis behavior and flash photolysis.…”
Section: Strain For Transformation-h Salinarum Strain Pho81wrmentioning
confidence: 99%
“…In addition, transient movement of helix F in ppR and receptort ransducer signal transfer were analyzed by means of electron paramagnetic resonance study on spin-labeled ppR and Htr II and their complex [10,11]. In contrast, we have demonstrated that a site-directed solid-state 13 C nuclear magnetic resonance (NMR) approach provides an alternative means to delineate conformation and dynamics of 13 C-labeled bR as a typical membrane protein at ambient temperature, once resolved 13 C signals, if any, could be assigned to certain residues of interest utilizing site-directed mutants [12^14] and conformation-dependent displacement of 13 C chemical shifts [15,16]. This approach turned out to be especially useful as a complementary means to di¡raction studies in which structural data of surfaces such as C-or N-terminals as well as loop regions are in many instances lost owing to a disordered or motionally averaged state [12^14].…”
Section: Introductionmentioning
confidence: 99%
“…[3-13 C]Ala, [1-13 C]Val-labeled ppR with a histidine-tag at the C-terminus expressed in Escherichia coli BL21 (DE3) strain was grown in the M9 medium to which 13 C-labeled L-Ala and L-Val were added and solubilized with 1.5% n-dodecyl L-D-maltoside (DM), followed by pu-ri¢cation with Ni-NTA resin (Qiagen) as described previously [15]. The puri¢ed protein was mixed with lipid ¢lm of egg PC (1:50 mol ratio) in which chloroform solvent was evaporated and DM as detergent was removed with Bio-Beads (SM2; Biorad) to yield ppR incorporated into egg PC bilayer.…”
Section: Introductionmentioning
confidence: 99%